Pathological neutrophil extracellular traps hinder postoperative anal fistula wound healing and are attenuated by Zuoqing granule via suppression of the Nox4 pathway - Fang, Xiaoli; Deng, Heng; Li, Ming; Gao, Xiang; He, Chunrong; Liu, Hui (Frontiers in Immunology, 2026)
BackgroundThe impaired healing of postoperative anal fistula wounds often complicated by a contaminated environment and persistent inflammation. The key pathological immune events that sustain this chronic inflammatory milieu remain largely unknown. We hypothesized that dysregulated neutrophil extracellular trap (NET) formation (NETosis)—a potent driver of tissue damage—might be a pathological feature and potential therapeutic target.MethodsUsing a rat model of contaminated wounds akin to postoperative anal fistula, we characterized NETosis via immunofluorescence (CitH3/CD66b), transmission electron microscopy, and ELISA. The involvement of the Nox4/ROS/PI3K/Akt/PADI4 pathway was assessed. The therapeutic potential of Zuoqing Granule (ZQG), a clinically used traditional Chinese formulation, was evaluated both in vivo and in PMA-stimulated rat neutrophils in vitro. Bacterial burden were also assessed.ResultsWe identified pervasive NETosis as a pathological hallmark of non-healing anal fistula wounds, accompanied by a surge in pro-inflammatory cytokines (IL-2, IL-5, IL-6, IL-12, TNF-α) and a ~15.5-fold increase in bacterial load compared to controls. ZQG treatment dose-dependently accelerated wound closure, resolved inflammation, reduced bacterial burden, and suppressed NETosis by up to 75.1% at day 7. Mechanistically, ZQG inhibited the Nox4/ROS/PI3K/Akt/PADI4 axis. In vitro, ZQG reduced PMA-induced NETosis by 63.0% and superoxide production by 58.1%, comparable to Nox4 knockdown.ConclusionOur study establishes aberrant NETosis as a pathological feature and potential therapeutic target in anal fistula-like wounds. We further identify ZQG as a promising candidate therapy that alleviates this pathology by suppressing the Nox4/ROS/PI3K/Akt/PADI4 pathway, without compromising bacterial clearance.